Cost Optimization In The Scheduling On Heat Exchanger Cleaning Process - David Licindo; Renanto Handogo; Juwari Purwo Sutikno (Institut Teknologi Sepuluh Nopember, 2015)
Cost utility is very important in an industry, particularly in the chemical industry. For an industry that operates the heat exchanger in the production process, utility usage is determined by the maintenance of this devices, one of which is cleaning. Therefore, it is necessary to schedule the optimal cleaning in order to obtain optimum expenses as well. in this paper, a cost optimization model has been developed to obtain ideal scheduling that takes into account the time of cleaning with minimum targets utility costs. Simple case study problem will be given to show the application and the results